2015
DOI: 10.1016/j.ajhg.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Mutations in NALCN Cause a Syndrome Characterized by Congenital Contractures of the Limbs and Face, Hypotonia, and Developmental Delay

Abstract: Freeman-Sheldon syndrome, or distal arthrogryposis type 2A (DA2A), is an autosomal-dominant condition caused by mutations in MYH3 and characterized by multiple congenital contractures of the face and limbs and normal cognitive development. We identified a subset of five individuals who had been putatively diagnosed with "DA2A with severe neurological abnormalities" and for whom congenital contractures of the limbs and face, hypotonia, and global developmental delay had resulted in early death in three cases; t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(165 citation statements)
references
References 48 publications
8
152
0
3
Order By: Relevance
“…First, patients reported with mutations in NALCN have similar clinical features to our patient (3)(4)(5). Second, Sanger sequencing confirmed that the patient had this missense mutation, and that the unaffected parents and sister did not have (Fig.…”
Section: To the Editormentioning
confidence: 66%
See 1 more Smart Citation
“…First, patients reported with mutations in NALCN have similar clinical features to our patient (3)(4)(5). Second, Sanger sequencing confirmed that the patient had this missense mutation, and that the unaffected parents and sister did not have (Fig.…”
Section: To the Editormentioning
confidence: 66%
“…Recessive mutations predominantly cause hypotonia and severe intellectual disabilities like infantile neuroaxonal dystrophy (1,2). Meanwhile, dominant mutations are all de novo, and cause congenital contractures of the limbs and face, hypotonia, and global developmental delay syndrome, or intellectual disability, ataxia and arthrogryposis (3)(4)(5). Thus, both recessive and dominant mutations might cause a severe phenotype in childhood.…”
Section: To the Editormentioning
confidence: 99%
“…Sensory impairments may have artificially reduced some scores for patients with FSS who were considered ‘average’ or ‘borderline’. While certain patients with FSS with mental retardation, hypotonia and early death exhibit missense allelic variations in the sodium leak channel, non-selective (NALCN),22 our clinical experience with many patients of different ages and socioeconomic backgrounds has shown that higher intelligence, relative to other family members, may represent a strong feature in a subset of patients with FSS without NALCN allelic variations or repeated hypoxia. Higher intelligence in this subset of patients with FSS may be the first association of higher intelligence with a pathological entity, and after many years of observation, we feel this possible association can no longer be ignored and warrants further inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…These infants were found to have mutations in NALCN and KIAA0586, respectively, with both genes having been associated with disease this year. [26][27][28][29] NGS panel containing known disease genes performed for these two infants in 2014 would have returned a negative result. Identifying the causative mutations would have required retesting because new genes were described in the literature and incorporated into commercially available tests.…”
Section: Discussionmentioning
confidence: 99%